Advance in placenta drug delivery: concern for placenta-originated disease therapy. (31st December 2023) - Tang, Miao; Zhang, Xiao; Fei, Weidong; Xin, Yu; Zhang, Meng; Yao, Yao; Zhao, Yunchun; Zheng, Caihong; Sun, Dongli
Abstract: In the therapy of placenta-originated diseases during pregnancy, the main challenges are fetal exposure to drugs, which can pass through the placenta and cause safety concerns for fetal development. The design of placenta-resident drug delivery system is an advantageous method to minimize fetal exposure as well as reduce adverse maternal off-target effects. By utilizing the placenta as a biological barrier, the placenta-resident nanodrugs could be trapped in the local placenta to concentrate on the treatment of this abnormal originated tissue. Therefore, the success of such systems largely depends on the placental retention capacity. This paper expounds on the transport mechanism of nanodrugs in the placenta, analyzes the factors that affect the placental retention of nanodrugs, and summarizes the advantages and concerns of current nanoplatforms in the treatment of placenta-originated diseases. In general, this review aims to provide a theoretical basis for the construction of placenta-resident drug delivery systems, which will potentially enable safe and efficient clinical treatment for placenta-originated diseases in the future.